2018
DOI: 10.4049/jimmunol.1701390
|View full text |Cite
|
Sign up to set email alerts
|

Intravesicular Acidification Regulates Lipopolysaccharide Inflammation and Tolerance through TLR4 Trafficking

Abstract: TLRs recognize pathogen components and drive innate immune responses. They localize at either the plasma membrane or intracellular vesicles such as endosomes and lysosomes, and proper cellular localization is important for their ligand recognition and initiation of signaling. In this study, we disrupted ATP6V0D2, a component of vacuolar-type H adenosine triphosphatase (V-ATPase) that plays a central role in acidification of intracellular vesicles, in a macrophage cell line. ATP6V0D2-deficient cells exhibited r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 58 publications
2
27
1
Order By: Relevance
“…The role of Arf6 in TLR signaling was confirmed in a study that demonstrated an essential role for Arf6 and the V-type ATPase in TLR responses [141]. In this study, ARF6-KO RAW264.7 mouse macrophage cells show a reduced LPS-induced activation of NF-κB and IRF3 and reduced LPS-induced IL-6 and interferon-β expression.…”
Section: The Crucial Role Of Arf6 In Tlr Signalingsupporting
confidence: 73%
See 2 more Smart Citations
“…The role of Arf6 in TLR signaling was confirmed in a study that demonstrated an essential role for Arf6 and the V-type ATPase in TLR responses [141]. In this study, ARF6-KO RAW264.7 mouse macrophage cells show a reduced LPS-induced activation of NF-κB and IRF3 and reduced LPS-induced IL-6 and interferon-β expression.…”
Section: The Crucial Role Of Arf6 In Tlr Signalingsupporting
confidence: 73%
“…In this study, the effects of Arf6 were linked to the interaction of Arf6 with the multimeric V-type ATP-ase [141]. Arf6 interacts with the c subunit of the V-type ATPase, while ARNO interacts with the a subunit [141,142,143].…”
Section: The Crucial Role Of Arf6 In Tlr Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…RT-PCR was performed with the following primers: Mtm1, sense 5Ј-ATCTTAGGAG-GATCGCAACG-3Ј, reverse 5Ј-TACCGACAAGAGGCTGA-CTG-3Ј; Mtmr1, sense 5Ј-TCCATTTATGGGAGCAGTGA-3Ј, reverse 5Ј-TGCACCAATCTTCTCCACTC-3Ј; Mtmr2, sense 5Ј-AGCAGAAATGGAGGAACCAG-3Ј, reverse 5Ј-CGCTCCATGCTCTTGAAATA-3Ј; Mtmr3, sense 5Ј-TGGG-AATGTATTCTGCTCCA-3Ј, reverse 5Ј-CAATGCTG-GAGCTTGTAGGA-3Ј; Mtmr4, sense 5Ј-TGTGTCCT-GGAAATGAAGA-3Ј, reverse 5Ј-AAACTGTTCAGGTGGC-TTCC-3Ј; Mtmr6, sense 5Ј-TTCCGGTCCTATCCTACTGC-3Ј, reverse 5Ј-TGAAGCAAATGCTCATCCTC-3Ј; Mtmr7, sense 5Ј-CCAGTTTGGGAACTTCCTGT-3Ј, reverse 5Ј-GGCAGCTCGATTCTTCCACA-3Ј; Mtmr8 sense 5Ј-GGCT-CTCTGGGTACCATCAT-3Ј, reverse 5Ј-GAGTGGACAAT-GCCTCAATG-3Ј. Primer for Ifnb, Il6, Il10, Cxcl10, and 18s were described previously (33,34).…”
Section: Rna Isolation and Rt-pcrmentioning
confidence: 99%
“…MTMR3 and MTMR4 were amplified from mouse cDNA and were subcloned into pFLAG-CMV2 (Sigma). Other plasmids were described previously (33). After 24-h transfection, luciferase activity was measured as described previously (33,34).…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%